2021
DOI: 10.21037/apm-21-10
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of ultrasound-guided above-knee lateral approach for popliteal sciatic nerve block in surgeries below the knee: a randomized controlled trial

Abstract: Background: Ultrasound guidance has become a standard method for detection of nerve structures in regional anesthesia. During ultrasound-guided blockade, to identify anatomical structures is crucial but can be challenging. In clinical practice, we find a wide difference in the visibility score of the sciatic nerve (SN) through different approaches. This study aimed to compare SNB through the anterior and above-knee lateral approach in terms of identification ease, performance efficacy, and safety.Methods: Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…For instance, Van Elstraete et al reported that the first attempt to locate the sciatic nerve was successful in only 7 of 20 patients (35.0%), 18 while Zhu et al reported that a satisfactory position was achieved during the first attempt in only 8 of 26 patients (30.8%), and 8 of 26 patients (30.8%) required more than two attempts to obtain a satisfactory position. 16 In the present study, we obtained a satisfactory position during the first attempt in 19 of 26 patients (73.1%), and only one patient (3.8%) required three attempts to obtain a satisfactory position. The reason for the repeated punctures in that patient might have been related to the age (over 70 yrs) or higher BMI (32 kg/m 2 ).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…For instance, Van Elstraete et al reported that the first attempt to locate the sciatic nerve was successful in only 7 of 20 patients (35.0%), 18 while Zhu et al reported that a satisfactory position was achieved during the first attempt in only 8 of 26 patients (30.8%), and 8 of 26 patients (30.8%) required more than two attempts to obtain a satisfactory position. 16 In the present study, we obtained a satisfactory position during the first attempt in 19 of 26 patients (73.1%), and only one patient (3.8%) required three attempts to obtain a satisfactory position. The reason for the repeated punctures in that patient might have been related to the age (over 70 yrs) or higher BMI (32 kg/m 2 ).…”
Section: Discussionsupporting
confidence: 49%
“…Zhu et al reported that in 10 of their 26 patients (38.5%) who underwent the anterior approach, the obtained image of the SN had poor quality (visibility score <2). 16 Our new method uses two well-defined ultrasonographic landmarks, the AMM and the femur, which can be obtained easily at the level of the upper middle thigh. The AMM, which is attached to the femur, covers the sciatic nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Although we do not know the exact value, we think that a person with a higher BMI also has a higher SCAT value. We found only one other study that measured the depth of the SN from the same point as we did (Zhu et al, 2021). They conducted their study on living patients, and found the SN depth (which Zhu et al defined as the distance from the skin to the superficial SN surface) to be 5.53 cm, similar to that of Kendir et al's study.…”
Section: Discussionmentioning
confidence: 60%
“…Kendir et al also declared that the route of the needle passed through only the adductor magnus, and that no neurovascular structure was at risk of injury with this method. Zhu et al compared this method with an above-knee lateral approach and reported that this method required less time and fewer attempts to block the SN (Zhu et al, 2021). This method may be used when combining two blockades in selected patients.…”
Section: Introductionmentioning
confidence: 99%
“…Zou Yinghua et al validated an improved anterior sciatic nerve block approach in which the puncture needle is nearly perpendicular to the ultrasound beam during the puncture process, making the needle visualization clearer, enhancing the safety of the puncture process, and providing nerve block effects comparable to traditional anterior sciatic nerve block [62]. Zhu et al, through the lateral approach at the upper outer thigh, demonstrated that this approach has a higher puncture success rate, better analgesic effects, and similar safety to the traditional approach [66].…”
Section: Lower Limb Injuriesmentioning
confidence: 99%